Aplikasi Teknik NGT (Nominal Group Technique-Teknik Kumpulan Nominal) dalam penilaian elemen model pembangunan profesionalisme pengurusan Pendidikan Islam - Habibah @ Artini Ramlie; Zaharah Hussin; Saedah Siraj; Norshahrul Marzuki Mohd Nor (2018)
This article discussing about Nominal Group Technique (NGT) in assessment of an Islamic Education teaching professionalism model. The objective is to determine to what extent this technique can adopted in assessing the elements of the main component of themodel. This technique was conducted in final phase of researcher’s research about the development of an Islamic education teaching professionalism model based on ‘Riadhah Ruhiyyah’ to identify the usability of that model. The findings show this technique can help the researcher to gain the data in simple and fastest way becausethe usability of the model can acquire directly from the items percentage score.